Sie sind auf Seite 1von 22

# Chapter 1

NUMERICAL SERIES
1. Sequences. 2. Definitions. General Criteria 3. Series with Nonnegative Terms. 4. Approximate Computation of Sums.. 5. Improper Integrals and Series 6. Infinite Products
1 17 28 38 42 59

7. SOLVED PROBLEMS
Exercise 38. (a) lim n ln n = 1
n

(b) lim n n! =
n

(c) lim ln n! = 1
n n

## (d) lim (f) lim

1n 4 ( n + 1)( n + 2)...( n + n ) = n n e
(g) lim
(n!) 2 =0 n ( 2n)!

(e) lim n
n

sin k
k =1

=0

( 2n) n =0 n ( 2n )!

(h) lim

## (i) lim n 1n + 2 n + ... + n n =

n

ln n! =1 n n ln n 1 n 1 (j) lim =2 n n k =1 k

(k) lim n + k n + k =
n k =1

(l) lim
n

1 n

n
k =1

k n+k

2(2 2 ) 3

Solutions: (a) Using Cauchys criterion we have: 1 1 ln(1 + ) ln n + ln(1 + ) ln(n + 1) n = 1 + lim n =1 lim n ln n = lim = lim n n n n ln n ln n ln n .

64

(b) Analogously:

lim n n! = lim
n

(n + 1)! = lim (n + 1) = . n n n!

(c) Applying roots criterion, then Stolz-Cesaros criterion we obtain: ln(n + 1)! ln n!+ ln(n + 1) ln(n + 1) = 1 + lim = = lim lim n ln n! = lim n n n n ln n! ln n! ln n! n+2 ln ln(n + 2) ln(n + 1) = 1 + lim n + 1 = 1. 1 + lim n n ln(n + 1) ln(n + 1)! ln n! (d) Again, Cauchys criterion implies:

l = lim n
n

n

## (2n + 1)(2n + 2) n n n = lim = 4 lim( n +1 n n n +1 (n + 1) (n + 1)

Or, because:
l = lim e
n ln n

)n

= 4 lim
n

1 4 = . 1 e (1 + ) n n

(1+ n )
k =1

= lim e
n

1 n k ln(1+ ) n k =1 n

denoting

## f ( x ) = ln(1 + x ), f : [0,1] IR, k xk = k =

we have:

k , n

n k 1 n ln(1 + n ) = f ( k )( xk xk 1 ) , n k =1 k =1 This is a Riemann sum for the continuous, hence integrable function f, therefore:

65

lim

1 1 1 n k ln(1 + n ) = 0 f ( x) dx = 0 ln(1 + x) dx = n n k =1 1 1 0

## = ( x + 1)' ln( x + 1) dx = ( x + 1) ln( x + 1)

0 4

ln 4 4 1 x 0 = 2 ln 2 1 = ln , and l = e e = . e e

(e)

lim n
n

sin k
k =1

= lim
n

sin k sin k
k =1 k =1 n

n +1

= lim sin
n

n +1

=0.

(f)
a n +1 an =

( 2n) ; then: (2n)! (2n + 2) n +1 (2n)! (2n + 2)(2n + 2) n 1 = = = n (2n + 2)! (2n) (2n + 2)(2n + 1) (2n) n

Let: a n =

1 1 e e (1 + ) n < <1 (1) 2n + 1 2n + 1 3 n for all n IN* ; it follows that (a n ) is a decreasing sequence of positive numbers, hence it converges, i.e. there exists a 0 such that a = lim a n . But, from (1):
n

3a n +1 ea n 3a ea (3 e)a 0 a 0 , hence a = 0 .
n

(n!) 2 (g) Let a n = . Then: (2n)! a n +1 [(n + 1)!] 2 (2n)! (n + 1) 2 n +1 = = = ; 2 an (2n + 2)! (n!) (2n + 2)(2n + 1) 2(2n + 1) n +1 1 3n + 3 4n + 2 1 n n IN* , but: 2(2n + 1) 3 a 1 hence: n +1 < 1, n IN* , i.e. (a n ) is a decreasing sequence of an 3 positive numbers; therefore it is convergent. Let: a = lim a n 0 . But
n

## 3a n +1 a n 0 , and, for Consequently a = 0 .

n , we obtain 3a a 0 or

a 0.

66

(h) We have n ln n , hence we can apply Cesaro-Stolz criterion and we obtain: ln(n + 1) ln(n + 1)! ln n! ln n! lim = = lim = lim n n ln n n ( n + 1) ln( n + 1) n ln n n n[ln( n + 1) ln n ] + ln( n + 1) 1 ln( n + 1) = 1. = lim = lim n n n 1 n 1 n ln(1 + ) + ln(n + 1) ln(1 + ) + 1 n n ln(n + 1) (i) Applying Cauchys criterion then Cesaro-Stolz criterion we
obtain:
lim n 1n + 2 n + ... + n n = lim
n

## 1n + 2 n + ... + (n + 1) n +1 ( n + 2) n + 2 = = lim n n ( n + 1) n +1 1n + 2 n + ... + n n

= lim (
n

n + 2 n +1 1 n +1 ) (n + 2) = lim (1 + ) (n + 2) = lim e (n + 2) = . n n n +1 n +1 (j) Cesaro-Stolz criterion implies (since n ): n 1 1 k n +1 + n n n +1 lim k =1 = lim = lim = lim(1 + )=2. n n n +1 n n + 1 n n n + 1 ( n + 1 n) n

## (k) We observe that:

a n = n + k n + k = n +1 n + 1 n + 2 n + 2 ... 2 n 2n > 2 n n + 1 2 n n + 2 ... 2 n 2n >
k =1 n

>

2n

[( n + 1)( n + 2)...( n + n ) ,

## hence, from Cauchys criterion:

( n + 2)...( n + n )( 2n + 1)( 2n + 2) 2 ] = lim[2( 2n + 1)] 2 = ; lim a n lim[ n n n ( n + 1)( n + 2)...( n + n ) consequently: lim a n = .
1 1 n

## (l) We remark that:

67

sn =

1 n

n
k =1

k n+k

1 n k =1

k n 1+ k n

= f ( k )( x k x k 1 ) ,
k =1

k x ; hence s n , k = 0,1,..., n , f : [0,1] R, f ( x) = n 1+ x is a Riemann sum for the function f ; but f is a continuous function and: 1 1 1 x +11 1 1 x lim s n = f ( x) dx = ) dx = dx = dx = ( x + 1 0 0 0 0 n x +1 x +1 x +1
where x k = k =

2( x + 1) = 3

2( x + 1)

1 0

22 = 3

22

1 2 + 2 = (4 2 2 ) . 3 3

Exercise 39. Test the series for convergence using the definition: n +1 1 (a) , a IR \ Z (b) n n = 0 ( n + a )( n + a + 1) n =0 2 1 (c) arctan 2 n + n +1 n =0 20 n 16n 4 8n 3 16n 2 + 1 (e) (d) 2 n +1 n(n + 1)(4n 2 1) 2 9 20 n + 4 2 n +1 n =1 5 n =1 (f)

ln 1 + 2(n 1)
n =1

2(2n 1) . 2 + 1

Solutions. (a) The general term can be decomposed as: 1 1 1 an = = , ( n + a )( n + a + 1) n + a n + a + 1 and the partial sum of n-th order: n n 1 1 1 1 1 1 = = sn = k + a +1 a n + a +1 a k = 0 ( k + a )( k + a + 1) k =0 k + a therefore the series is convergent and its sum: 1 1 (n + a)(n + a + 1) = a . n =0

68

k +1 , we k k =0 2 consider the derivative of sum of a geometric progression: n n x x n+2 1 (n + 2) x n +1 (1 x) + x x n + 2 (k + 1) x k = ( x k +1 )' = ( )' = , 1 x (1 x) 2 k =0 k =0 1 and, for x = we obtain: 2 n+2 1 1 1 1 1 s n = 4(1 n +1 ) + n + 2 4( + ) = 4 , 2 2 2 2 2 2 therefore s n is convergent, i.e. our series converges and its sum is

## (b) For the partial sum of n-th order: s n =

n +1 = 4. n n =0 2 (c) Since: 1 (k + 1) k arctan 2 = arctan = arctan(k + 1) arctan k , k IN , 1 + (k + 1)k k + k +1 the partial sum n 1 s n = arctan 2 = arctan(n + 1) arctan 1 , 2 4 k + k +1 k =1
4; we write:

## and we conclude that our series is convergent and its sum is

If we mark a = 5 n and b = 4 n then the general term is: ab a 5a ab ab = = = an = 2 2 4b (a b)(5a 4b) a b 5a 4b 5a 9ab + 4b 5(a b)(a ) 5 hence the partial sum of n-th order is: n n 5k 5k 5 n +1 sn = ak = k k +1 = 5 n +1 = k 5 4 k +1 5 4 n +1 k =1 5 4 k =1 ; 1 = 5 5 1 = 4 4 1 ( ) n +1 5 20 n therefore the series is convergent and: n +1 = 4. 4 n +1 )(5 n 4 n ) n =1 (5

(d)

69

(e) The general term a n can be decomposed in simple fraction: 16n 4 8n 3 16n 2 + 1 A B C D E , an = = + + + + 2 2 n ( n + 1)( 2n 1) ( 2n + 1) n n + 1 2n 1 2n + 1 ( 2n + 1) 2
and, after calculations, we obtain: 16 + 8 16 + 1 11 4 +1 = 1, A = 1, B = = 1, E = 3 9 1+1 4 +1 = 1, C = D = 0 ; F= 1 therefore: n n 1 1 1 1 1 1 sn = a k = + = 1 1+ 0 2 2 k + 1 ( 2k 1) n +1 ( 2k + 1) ( 2n + 1) 2 k =1 k =1 k consequently the series is convergent and its sum is 0.

(f) The partial sum of n-th order: n n 2( k 1) 2 + 1 + 4k 2 2k 2 + 1 sn = ln = ln = ln( 2n 2 + 1) 2 2 2( k 1) + 1 k =1 k =1 2( k 1) + 1 when n and the series is divergent. Exercise 40. Check whether the necessary condition for convergence is fulfilled: 1 1 1 3 5 7 (a) + + + ... (b) + + + ... 5 11 16 5 11 16 Solutions. (a) The general term of our series: 1 an = 0 when n , hence the necessary condition for 5n + 1 a n 1 (0, ) , hence, convergence is verified; however: n = 1 5n + 1 5 n the series has the same nature with harmonic series and, therefore is divergent. 2n + 1 2 (b) Here a n = 0 , hence the series diverges. 5n + 1 5

70

Exercise 41. Test the series for convergence by means of the integral test: 1 2 3 1 2 3 (a) 3 + 3 + 3 + ... (b) + + + ... 2 2 2 3 4 1+1 1+ 2 1 + 32 1 1 1 + + + ... (c) 2 2 2 ln 2 3 ln 3 4 ln 2 4 Solutions. (a) The general term is: x n an = = f ( n ) , where f ( x) = , f : [1, ] IR + , 3 ( n + 1) ( x + 1) 3 and the generalized integral: x f ( x)dx = dx = 1 1 ( x + 1) 3 x +11 = dx = ( x + 1) 2 ( x + 1) 3 dx = 3 1 ( x + 1) 1 1 1 1 1 1 = + = = < ; 2 1 x + 1 2( x + 1) 2 4 4 therefore series converges. The same conclusion can be obtained a 1 observing that and a n has the same nature n 1 (0, ) . 1 n n (b) The general term can be written: n x an = = f (n) , where f ( x) = 2 , f : [1, ] IR , 2 1+ n x +1 1 2x 1 and f ( x )dx = 2 dx = ln( x 2 + 1) |1 = , 1 2 1 x +1 2

hence

a n n2 diverges. Besides: n = 2 1 (0, ), and after 1+ n2 1 n +1 n =1 n comparison test, the series diverges. 1 (c) We have: a n = = f (n) , where n ln 2 n 1 f : [2, ] (0, ) , f ( x) = , and: x ln 2 x

71

d (ln x ) dx 1 1 = = < ; |2 = 2 2 ln 2 ln x x ln x 2 ln x

consequently

a
n=2

## obtained applying Cauchys condensation criterion: since

a n 0 (n ) the series:

a
n=2

## and (generalized harmonic

1 1 1 = 2 2 < 2 n (ln 2 n ) 2 ln 2 n =1 n n=2 n=2 series, = 2 > 1 ) have the same nature.

2n a = 2n

Exercise 42. Test the series for convergence using DAlemberts test: 2 4 6 1 2 1 2 3 (a) + + + ... (b) 1 + + + ... 3 9 27 1 3 1 3 5 1 3! 5! (c) + + + ... 2 24 246 Solutions. (a) We have the general term a n =
and

2n , n IN* , n 3

a n +1 2(n + 1) 3 n n + 1 1 = = <1 , n +1 2n 3n 3 an 3 2n hence the series n is convergent. n =1 3 a 2n + 1 n! (b) a n = , and n +1 = 1 , hence 2n + 2 (2n 1)!! an DAlamberts test is inconclusive. a 2n + 2 1 n n( n 1) = n( 1) = < 1 and, according to But a n +1 2n + 1 2n + 1 2 Raabe-Duhamels test, the series diverges.

Exercise 43. By comparing with a harmonic series or a decreasing progression, test the series for convergence:

72

(a)

1 2

2 3

3 4

4 5

+ ...

(b)

1 1 1 + + + ... ln 2 ln 3 ln 4

(c) 1 +

1 1 + + ... 2 5 3 52

Solutions. (a) The general term is 3 a 1 1 n , and , for b n = 6 we have n = 1 1 ; an = bn n +1 n n6 But bn is the general term of harmonic series with
1 < 1 and the series 6 diverges too.

b
n =1

(b) we obtain:

## Using the well known inequality ln x < x , for all x > 1

an =

1 1 > , n IN , n 2 , ln n n

ln n
n =2

diverges.

(c)
an 1
n 1

## Here the general term is a n = and the geometric series

1 , n IN* ; but: n 1 n5

5 1 ( q = (1,1) ), hence 5

1
n 1

converges

n5
n =1

1
n 1

is a convergent series.

## Exercise 44. Test the series

convergence where:

an and
n =1

a
n =1

2 n

for

(a) a n =

73

(c) a n =

## Solutions. (a) For a = 0 the both series converge. Let a 0 .

Then:
a n +1 a 2+ (n + 1) 2 n +1 = a a , n 21 = a2 a2 2 an x + n +1 an ( x + n + 1) hence, by DAlambert' test, the both series converge when a (1,1) and diverge for a (,1) (1, ) . a nx x + n +1 a = + 1 . Then: n n = n 1 = x, a n +1 n +1 n +1 hence by Raabe-Duhamels test, a n converges for x > 1 , and

Let

## diverges for x [0,1) ; if x = 1 , a n =

1 a n , hence if a = 1 the series n +1 diverges (harmonic series) and for a = 1 converges (Leibniz 2 criterion). Analogously for x > 1 , a n converges, and if x [0,1) 1 and (n + 1) 2

2 diverges. If x = 1 , a n =

2 n

converges (generalized

harmonic series).

ln x , f : [1, ) IR . The function is a x 1 ln x < 0 , if x (e, ) ; decreasing one on [e, ] , since f ' ( x) = x2 ln n therefore is a decreasing sequence and, by Leibniz criterion, n ln n 1 ln n ( 1) n n converges. We remark that: n > n , n IN , n > 2 and n =1 1 ln n n diverges, hence by comparison test it follows that (1) n n n =1 n =1 is semiconvergent (the series is not absolutely convergent). Since:

(b)

Let f ( x) =

74

2 an ln 2 n = 0 , when n , and 1 n

n =1

1 n
3 2

2 a n , converges,

## we conclude, by comparison test, that the series

a
n =1

2 n

converges.

(c) Of course the both series are convergent for a = 0 . Let a 0 . Then: 2 a n +1 (4n + 1) 2 2 a n +1 4n + 1 = a a , and 2 = a a; an 4n + 3 (4n + 3) 2 an D Alamberts criterion implies that the series converge for a (1,1) and diverges for a (,1) (1, ) . If a {1,1} since
a2 (4n + 3) 2 16n 2 + 8n n 2n 1 = n 1 = 16n 2 + 8n + 1 < 1 , Raabe-Duhamels (4n + 1) 2 a n +1

## test implies that

a
n =1

2 n

diverges. For

a 2n 1 4n + 3 < 1 , hence a n a = 1 , n n 1 = n 1 = a 2 4n + 1 4n + 1 n =1 n +1 a diverges, and for a = 1 , since n +1 < 1 , for all n IN* , Leibniz an

## criterion implies the convergence of the series

a
n =1

Exercise 45. Test the series with the general term sin na n 1 un = , a IR , (n>1) for convergence. n 1 i = 2 ln i Solution. If a {b | k Z } , u n = 0 and u n = 0 .

75

1 n 1 and an = sin na . We verify n 1 i =2 ln i the conditions of Abels test. First, by Stolz-Cesaros criterion we have: 1 ln(n + 1) lim n = lim = 0 ; moreover: n n n ( n 1)
Let a {k | k Z } , n =

< n = n +1 = + + ... + + ... + n ln 2 ln 3 n 1 ln 2 ln(n + 1) ln n 1 1 1 1 (n 1) ln 2 + ... + ln(n + 1) < n ln 2 + ... + ln n n 1 1 1 < + ... + , ln(n + 1) ln 2 ln 3 ln(n + 1) and the last inequality is true, since, ln k < ln(n + 1) for k {2,3,..., n} ; therefore: ( n ) is a decreasing sequence, and n 0 . (1) Moreover: ( n + 1)a na sin sin n 1 (2) ak = sin a + sin 2a + ... + sin na = 2 a 2 a k =1 sin sin 2 2 hence, from (1), (2) and Abels test we conclude that the series u n = n a n converges for all a IR .

1 1

1 1

## Exercise 46. Study the nature of series:

n (a) cos 4 n =13

## (2n 1)!! (b) ! n =1 (2n ) !

, x IR

(c)

1 , x [0, ) n n =1 n + x n . Since: 4

## Solutions. (a) Let a n = cos

76

a8 n 1 and a 4 n + 2 0 , when n it follows that a n 0 , and, from divergence criterion, the series / diverges.

## (2n)!! 2n + 1 1 wn = , 2n 2 (2n 1)!! 2n + 1 2

whence:
( 2n 1)!! 2 2n + 2 2 2 cn := an = =: bn 2 ( 2n + 1) ( 2n )!! ( 2n + 1) (1) But:
2

(2)

n2

1 =

(3)

## series is convergent if and only if > 2 .

n 2 From (1), (2), (3) and comparison test it follows that series bn , cn and a n have the same nature. Consequently our

8. EXERCISES
Exercise 1. Prove that: (a)

na
n =1

n 1

1 (1 a ) 2

for

77

## (2n + 1)!! = 2 (n 1)! = 1 (2n + 2)!! = 2 (b + 1)(b + 2)...(b + n) = b a 1 for b a > 1

n =1 n =1 n =1 n =1

(2n 1)!!

(a + 1)(a + 2)...(a + n)

a +1

## n2 n3 = 2 + 2e , = 5e (it is known that n! n =1 n =1 n !

n! = e ).
n =0

Exercise 2. Check whether the necessary condition for convergence is fulfilled: 1 2 3 (a) + + + ... 2 3 4 1 3 5 (b) + + + ... 2 4 6 2 4 6 (c) + + + ... 3 5 7 1 1 1 (d) + + + ... 3 5 7 2 4 6 (e) + + + ... 3 9 27 Exercise 3. Test the series for convergence by means of the integral test: 1 1 (a) 1 + + + ... 5 9 1 1 (b) 1+ + + ... 4 7 1 2 3 (c) + + + ... 2 3 33 4 3 1 1 1 (d) + + + ... 2 2 1 + 1 1 + 2 1 + 32

78

## 1 2 3 + + + ... 2 2 1 + 1 1 + 2 1 + 32 1 1 1 + 2 + 2 + ... 2 2 1 4 1 6 1 1 1 1 + + + ... 2 2 2 ln 2 3 ln 3 4 ln 2 4

Exercise 4. Test the series for convergence using dAlamberts test: 2 4 6 (a) + + + ... 3 9 27 2 4 8 (b) 1 + + + + ... 2! 3! 4! 3 32 33 (c) 1+ + + + ... 2 3 2 2 5 23 7 1 3! 5! 7! (d) + + + + ... 2 2 4 2 4 6 2 4 6 8 1 5 9 13 (e) + + + + ... 3 2 32 3 33 4 34 Exercise 5. Using criteria of comparison test the series for convergence: 1 1 (a) 1+ + + ... 2 3 1 1 (b) 1+ + + ... 2 5 3 52 1 1 1 (c) + + ... ln 2 ln 3 ln 4 1 1 1 (d) + + + ... 2 4 1+ a 1+ a 1+ a6 1 1 (e) 1+ + + ... 1+ 2 1+ 2 + 3 3 (f)
3 7 2

2
5 3

2 + 2

7 3 2

3 + 5 33

+ ...

79

## (a) (b) (c) (d) (e) (f)

Exercise 6. Find the sum of the series (if it converges): 1 1 1 + + + ... 1 2 2 3 3 4 1 1 1 + + + ... 1 4 4 7 7 10 1 1 1 + + + ... 1 3 2 5 3 7 1!! 3!! 5!! 7!! + + + + ... 4!! 6!! 8!! 10!! 20 20 2 20 3 + 3 + 4 + ... (5 2 4 2 )(5 4) (5 4 3 )(5 2 4 2 ) (5 4 4 )(53 4 3 )
6 62 63 arctg + arctg + arctg + ... 2 4 + 39 2 42 + 3 92 2 43 + 3 93

Exercise 7. Test the series with the general term a n for convergence: 2 ( n! ) 2 an n (a) )n ; a n = n 2 ; (b) an = , a 0 ; (c) a n = ( n 2 n +1 n 4k 3 1 (2n 1)! (d) ; (e) an = ; (f) an = ; an = n 13 15 (n!) 2 k =1 4k 1 n ln n (g) (i) (k) (m) (n) (p)
1 ln(n 2 + 1) , , a IR ; (h) an = (1) n ; n ln a n n 1 (2n 1)!! ; (j) an = sin nx, x IR ; an = (1) n ln n 2n!! cos nx ; (l) an = a ln n , a > 0 ; an = 2 n +1 1 1 an = a bn , bn = 1 + + ... + , a > 0 ; 2 n n2 an = a n n!, a > 0 ; (o) an = a n ( 2 ) n , a > 0 ; n +1 2 n n a (a + 1)...(a + n) ) , a > 0; (r) an = , a, b > 0; an= an ( n +1 n! n b an =

80

(s)

## ln x (2n 1)!! a b 1 (u) a n = (1) n 2 n ; (v) an = ( ) n , a, b IR; na (2n)!!

(x) an =

an =

cos nx sin

x n , x IR ;

(t) a n =

10 n ; 3n

na , a, b IR 1 + n + nb

## Exercise 8. Evaluate the error if we replace the sum of series

with s 2 , s3 , s 4 , where s n = ac , n I* .
1 1 1 ; (b) (1) n1 n ; (c) (1) n ; n! n n! n =1 n =1 n =1 n 1 1 (d) 2 2n2 ; (e) (2n 1)!! ; (2n)!! . n =1 n =1 n =1 Exercise 9. Find a minimal n I such the error in the approximation s s n is less than 10 3 , s, s n being the sum, respectively the nth partial sum of series given at the Exercise 8.

(a)

k =1

Exercise 10. Study the semi convergence of series: cos x n cos x (a) (1) n 2 , x IR ; (b) n (1) n n , x IR n =13 =131 (c) (f) (h)

(1)

n2 +n 2

(1) n1 n n =15

(1) n1
n =1

## (1) n1 cos nx ln(n + 1) , x [0, 2 ] . n =1

Exercise 11. Test the following series for convergence: 1 n (a) (ln n) (b)

(n ln n ln ln n)

81

sin 2
1

2 5 4

n 2 n + 1]

## Exercise 12*. Suppose

positive terms. Prove that

is a convergent series of

## an an+1 converges. (n + 1) 1 2 is a convergent series; form

Exercise 13*.

(1)
n =0

n +1

the square. Does this latter series converge? Do the same for the series

(1)
n =0

n +1

## (n + 1) 1 . You should get:

1 1 + ... + ). n 2 n =1 Why does this series converge or not converge? 2 (1) n+1 (n + 1) 1 (1 +

Exercise 14*. For what values of x IR does the series 1 1 1 n (1 + 2 + ... + n ) sin nx n =1 converge? Exercise 15*. If r (1,1) and p IN*, show that the series:
n = p +1

## n(n 1)(n 2)...(n p) r

converges.

Exercise 16*. Show that the series with the general term: 1 ( n + 2) 2 a n = ln n n ( n + 2) converges.

82

k = m +1

<

n 1

Exercise 17*.

(1)
n =0

and equal to + .

(1 + n) is
n =1

divergent

(1 +
n=2

(1) n ) = 1. n

(1 + n ) = +.
n =1

Exercise 21.

(n + 1)
n =1

n(n + 2)
2

1 = . 2

Exercise 22.

1 + tg
0

dx

4
1

x + [ x] dx
0

dx

are divergent

its value.

[ln x]dx
0

83

Exercise 25.

1 x dx = 1+ x

## Exercise 26. Show that Exercise 27. min( x 2 ,

0

0`

x(1 + x

arctn x
2

dx converges.

1 4 )dx = . 2 3 x

Exercise 28.

2[ x] + 3[ x]
1

dx

1 = . + [x ] 4
3

Exercise 29.
a b.

(x
0

## dx , for all a, b IR , = 2 2 + a )( x + b ) 2ab(a + b)

2

Exercise 30.

sin
0

dx = 2 2 . + cos 4 x

Exercise 31.

x 2 dx 2 x4 +1 = 4 . 0

## (a) (b) (c) (d) (e)

Exercise 32. Show that: x sin x cos 2 n = x , x IR - I n =1 1 1 (1 + ) and (1 ) ( IR) are convergent iff > 1. n n n =1 n =1 (n + 1)(n + 3) n(n + 4) = 4 n =1 1 1 (1 n 2 ) = 2 n =1 1 (1 + 22n ) = 2 n =0

84

(f) (g)*

n3 1 2 n3 + 1 = 3 n =1

2+
n =1

n n

= 0. (Hint

2+
k =1

k k

<

1 2 n

, n IN*).

85